Will Bitcoin Incarnate Satoshi Nakamoto's Vision of Depoliticized Money? - Phillips, Emir (Journal of Economic Issues, 2025)
Cryptocurrencies are oftentimes cast as future-oriented technological innovations that decentralize money, thereby liberating it from centralized governance and the political tentacles of The State; more specifically, as a trustless substructure, Bitcoin endeavors to operate irrespective of any social institutions. The protocols underpinning the platform are embedded directly into the network protocol, coupling the Bitcoin community towards technological determinism, a spell wherein technological artifacts can rudder both culture and society without the necessity of any political intermediation, whether by The State or Central Bank. Blockchain has focused too narrowly on providing a technological solution to the issue of scarcity and solving the double-spending problem. Problems involved in monetary and payment systems provide for a broad range of mechanisms supporting the circulation of money, which must be backed by the state for the scale and complexity of a modern economy. Cryptocurrencies such as Bitcoin are better perceived as a technological innovation that does not remove money from politics but rather is part of a struggle over the political status of money in an age of financialization. Money is a hybrid public-private institution, and technology alone cannot render the role of state institutions in monetary and payment systems obsolete.